Characterization of DON in IOM derived from M. aeruginosa and its removal by sunlight/immobilized TiO2 system. Issue 51 (6th May 2015) - Liu, Cheng; Wang, Jie; Chen, Wei; Zhu, Haoqiang; Bi, Hongkai
Abstract : Dissolved organic nitrogen (DON) is now considered as one of the most important precursors of nitrogenous disinfection byproducts (N-DBPs), and the algae cells were the main source of DON in eutrophic water sources. Abstract : Dissolved organic nitrogen (DON) is now considered as one of the most important precursors of nitrogenous disinfection byproducts (N-DBPs), and the algae cells were the main source of DON in eutrophic water sources. In this study, the characterizations of DON (especially proteins) in intracellular organic matter (IOM) were investigated. In addition, the DON removal by using sunlight/immobilized TiO2 was also studied. The results showed that in algae cells, about 185 kinds of proteins were found and the distribution of isoelectric points of these proteins was mostly in acidic side. Apo-α-phycocyanin and Apo-β-phycocyanin are the two main components, whose concentrations were 0.187 mg L −1 and 0.136 mg L −1, respectively. The removal rate of DON by sunlight/TiO2 system was about 29% after 7 hours irradiation, moreover, the system altered the molecular weight ranges of 30–80 kD to the range of 20–30 kD. Furthermore, proper photo-catalytic oxidation enhanced the coagulation efficiency significantly due to the direct removal and change of proteins.